Patient outcomes after hospitalisation with COVID-19 and implications for follow-up: results from a prospective UK cohort. Issue 4 (3rd December 2020) - Arnold, David T; Hamilton, Fergus W; Milne, Alice; Morley, Anna J; Viner, Jason; Attwood, Marie; Noel, Alan; Gunning, Samuel; Hatrick, Jessica; Hamilton, Sassa; Elvers, Karen T; Hyams, Catherine; et al.
Abstract : The longer-term consequences of SARS-CoV-2 infection are uncertain. Consecutive patients hospitalised with COVID-19 were prospectively recruited to this observational study (n=163). At 8–12 weeks postadmission, survivors were invited to a systematic clinical follow-up. Of 131 participants, 110 attended the follow-up clinic. Most (74%) had persistent symptoms (notably breathlessness and excessive fatigue) and limitations in reported physical ability. However, clinically significant abnormalities in chest radiograph, exercise tests, blood tests and spirometry were less frequent (35%), especially in patients not requiring supplementary oxygen during their acute infection (7%). Results suggest that a holistic approach focusing on rehabilitation and general well-being is paramount.